2006
DOI: 10.1186/1479-0556-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ribonuclease activity on the skin surface

Abstract: The rapid degradation of ribonucleic acids (RNA) by ubiquitous ribonucleases limits the efficacy of new therapies based on RNA molecules. Therefore, our aim was to characterize the natural ribonuclease activities on the skin and in blood plasma i.e. at sites where many drugs in development are applied. On the skin surfaces of Homo sapiens and Mus musculus we observed dominant pyrimidine-specific ribonuclease activity. This activity is not prevented by a cap structure at the 5'-end of messenger RNA (mRNA) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Another report demonstrated that freeze-dried naked mRNA is stable for at least 10 months under refrigerated conditions 160 . The stability of mRNA products might also be improved by packaging within nanoparticles or by co-formulation with RNase inhibitors 161 . For lipid-encapsulated mRNA, at least 6 months of stability has been observed (Arbutus Biopharma, personal communication), but longer-term storage of such mRNA–lipid complexes in an unfrozen form has not yet been reported.…”
Section: Therapeutic Considerations and Challengesmentioning
confidence: 99%
“…Another report demonstrated that freeze-dried naked mRNA is stable for at least 10 months under refrigerated conditions 160 . The stability of mRNA products might also be improved by packaging within nanoparticles or by co-formulation with RNase inhibitors 161 . For lipid-encapsulated mRNA, at least 6 months of stability has been observed (Arbutus Biopharma, personal communication), but longer-term storage of such mRNA–lipid complexes in an unfrozen form has not yet been reported.…”
Section: Therapeutic Considerations and Challengesmentioning
confidence: 99%
“…84 Thus, the efficacy of mRNA vaccines may benefit significantly from complexing agents which protect RNA from degradation. Complexation may also enhance uptake by cells and/or improve delivery to the translation machinery in the cytoplasm.…”
Section: Formulation Of Mrnamentioning
confidence: 99%
“…It has been shown that local injection of naked mRNA could lead to a specific immune response (1012). However, this strategy did not lead to high levels of protein expression, as naked mRNA molecules are immediately degraded by tissue nucleases (13). Since the negatively charged mRNA molecules cannot enter antigen-presenting cells directly, mRNA-based vaccine is usually prepared by transfecting mRNA molecules into patient-derived dendritic cells (DCs) by electroporation (14, 15).…”
Section: Introductionmentioning
confidence: 99%